Economic analysis and Monte Carlo simulation of community wind generation in rural western Kansas - Halling, Todd (Kansas State University, 2011)
Energy costs are rising, supplies of fossil fuels are diminishing, and environmental concerns surrounding power generation in the United States are at an all-time high. The United States is continuing to push all states for energy reform and where better for Kansas to look than wind energy? Kansas is second among all states in wind generation potential; however, the best wind generation sites are located predominantly in sparsely populated areas, creating energy transportation problems. Due to these issues interest in community wind projects has been increasing. To determine the economic potential of community wind generation a distribution system in rural western Kansas where interest in community wind exists was examined and a feasibility study based on historical data, economic factors, and current grid constraints was performed. Since the majority of the load in this area is from pivot-point irrigation systems, load distributions were created based on temperature ranges instead of a linear progression of concurrent days. To test the economic viability three rate structures were examined: flat energy rate, demand rate, and critical peak pricing. A Monte Carlo simulation was designed and run to simulate twenty-year periods based on the available historical data; twenty-year net present worth calculations were performed to ensure economic viability. A sensitivity analysis was then performed to examine the effects of change in turbine size and energy rate scale. Finally, an energy storage analysis was performed to examine the economic viability of various sizes of battery storage systems.
Keywords: Community wind generation; Feasibility study; Economic analysis; Monte Carlo simulation; Sensitivity analysis; Energy storage analysis; Electrical Engineering (0544); Energy (0791)